Knowledge of obstetric danger signs among pregnant women attending antenatal clinic at rural health training centre of a medical college in Hyderabad - Bhumi, Manoj Aravind; Chajhlana, Sunil Pal Singh (International Journal Of Community Medicine And Public Health, 2018)
Background: One of the major causes for the death of women is due to maternal mortality. Around 529,000 women die annually from maternal causes (World Health Organization (WHO) estimate) Majority of these deaths occur in the less developed countries. An Indian woman dies from complication related to pregnancy and child birth for every 7 minutes. For every woman who dies =30 more women suffer injuries, infection and disability. In Sub-Saharan Africa, where one of every 16 women dies of pregnancy related causes during her lifetime, compared with only 1 in 2,800 women in developed regions. Raising awareness of women about obstetric danger signs would improve early detection of problems and helps in seeking timely obstetric care. Methods: A cross sectional study was conducted among pregnant women who attended antenatal clinics between May 2014–August 2014 at field practice areas of RHTC, KAMSRC. A total 274 pregnant women had given consent and participated in the study. Data was collected by interview in local language and a predesigned and pretested questionnaire was used which include socio demographic profile, parity, ANC visits, gravid, knowledge regarding danger signs during pregnancy, post-partum period. Socio-economic status was assessed according to Modified Kuppuswamy’s classification (as per June 2015 CPI). Results: About 35.7%, pregnant women have good awareness 21.2%, average and 43% have poor knowledge about danger signs of pregnancy. Pregnant women in the age group of >30 years, educational status and occupational status of pregnant women and their husbands and pregnant mothers who had regular antenatal check-ups had significant associations with the awareness of obstetric danger. Conclusions: Our study concludes that there is need of creating awareness and increasing the knowledge of women about obstetric danger signs.